TOPICAL SOLID LIPID NANOPARTICLES BASED GEL OF LAVENDER ESSENTIAL OIL FOR ANTI‑INFLAMMATORY ACTIVITY - PALLAVI M CHAUDHARI; VAISHNAVI M BIND (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the study was to formulate and evaluate and perform an optimization study of lavender essential oil loaded solid lipid nanoparticles (SLNs) based gel. Materials and Methods: SLNs were prepared by the hot homogenization technique. A total of eight formulations were formulated as per 23 factorial design by design expert 11 software. The formulated SLNs were further evaluated for particle size, entrapment efficiency, drug release profile. After evaluation, the optimized batch was further used for formulating gel. The formulated gel was further subjected to ex vivo studies. Results: After the evaluation of all the parameters, batch 7 was found to be optimized. Batch 7 was found to have the lowest particle size of 30.91±0.30, higher entrapment efficiency of 89.99±0.87, and higher drug release of 90.41±0.55. It was further used for formulating gel which was found to be consistent, homogenous, smooth, and spreadable. The % inhibition of the formulated SLN based gel was found to be 28±0.1%. Conclusion: The SLNs were prepared and were formulated into the gel. The gel showed anti-inflammatory activity.